Intensive and Integrated Assistance in the Development of the Tourism Sector in Racitengah Village, Sidayu District, Gresik Regency (Infrastructure Modeling) - Mirza Dwinanda Ilmawan; Rosa Rilantiana; Aditya Narendra Wardhana; Marisya Mahdia Khoirina; Lisa Risfana Sari; ma'rifa tul ulya; Khusniya Pratama Putri; Rio Renaldo; Bayu Alfiansyah (OJS Universitas Muhammadiyah Gresik, 2021)
The purpose of this community service activity in the assisted villages is to create a mapping model for the tourist vehicle of Raci Tengah Village, Sidayu Gresik District. The resurrected village rides are game tourism vehicles for children to improve the economic activity of local residents. This modeling is expected to be able to provide an overview of the mapping of the tourism vehicle sector and also the infrastructure sector supporting game tourism for these children. Keywords: Tourism Rides, Facilities